Evaluation of the Clinical Effectiveness of Oseltamivir for Influenza Treatment in Children - Qin, Jianru; Lin, Jilei; Zhang, Xiangfei; Yuan, Shuhua; Zhang, Chiyu; Yin, Yong (Frontiers in Pharmacology, 2022)
Objective: To estimate the clinical effectiveness of oseltamivir in children with different subtypes of influenza virus infection. Methods: A total of 998 children with acute respiratory infection were enrolled from January to March 2018, and were divided into influenza A, influenza B, influenza A+B, and non-influenza infection (IV-negative) groups. Influenza-like symptoms and duration of fever were evaluated and compared between oseltamivir-treated and non-treated groups. Results: There were no significant difference in the reduction in total febrile period and duration of fever from the onset of therapy between the oseltamivir treated and non-treated children infected with influenza A (p=0.6885 for total febrile period and 0.7904 for the duration of fever from the onset of treatment), influenza B (p=0.1462 and 0.1966), influenza A+B (p=0.5568 and 0.9320), and IV-negative (p=0.7631 and 0.4655). The duration of fever in children received oseltamivir therapy within 48 h was not significantly shorter than that beyond 48 h (p>0.05). Additionally, percentages and severities of influenza-like symptoms, including headache, myalgia, fatigue, bellyache, vomiting, diarrhea, sore throat, cough, and coryza were not decreased and alleviated after treatment of oseltamivir. Conclusion: Oseltamivir treatment does not significantly shorten the duration of fever, nor does it significantly relieve influenza-like symptoms in children with infection of influenza.